2023
DOI: 10.1177/13524585231199820
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between age and disease-modifying treatments in influencing infection risk in multiple sclerosis

Sarah Lena Susanna Jacober,
Giulio Disanto,
Rosaria Sacco
et al.

Abstract: Background: Disease-modifying treatments (DMTs) can increase the risk of infections in multiple sclerosis (MS). Aged individuals are usually excluded from clinical trials, and there is uncertainty regarding safety of immunosuppressive DMTs in these patients. Objective: To investigate the association of DMTs, ageing and other clinical variables with risk of infections in MS patients. Methods: Prospective single-centre observational study collecting information on occurrence, type and grade of infections in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…A 1-year observational study in MS ( N = 503) reported an increased risk of infections with orally administered DMTs (incidence rate ratio [IRR] 2.04 [95% CI 1.19–3.49]) and monoclonal antibody DMTs (IRR 2.32 [95% CI 1.39–3.89) vs. a control group who received interferons, glatiramer acetate or no DMT [ 1 ]. The effect of treatment with monoclonal antibody DMTs (vs. other treatments) on infections was stronger in younger (IRR 5.90) vs. older (IRR 1.95) subjects in this analysis.…”
Section: Practical Considerations For Prescribing Cladribine Tablets ...mentioning
confidence: 99%
See 1 more Smart Citation
“…A 1-year observational study in MS ( N = 503) reported an increased risk of infections with orally administered DMTs (incidence rate ratio [IRR] 2.04 [95% CI 1.19–3.49]) and monoclonal antibody DMTs (IRR 2.32 [95% CI 1.39–3.89) vs. a control group who received interferons, glatiramer acetate or no DMT [ 1 ]. The effect of treatment with monoclonal antibody DMTs (vs. other treatments) on infections was stronger in younger (IRR 5.90) vs. older (IRR 1.95) subjects in this analysis.…”
Section: Practical Considerations For Prescribing Cladribine Tablets ...mentioning
confidence: 99%
“…Important demographic shifts are occurring in the population of people with relapsing multiple sclerosis (RMS). These include an increase in the overall age of this population, which is of potential importance as the efficacy of disease-modifying therapies (DMTs) has been reported to decrease, and the risk of infections has been reported to increase, as people with MS grow older [ 1 , 2 ]. It is therefore important to study the effects of individual DMTs in older and younger people with RMS separately.…”
Section: Introductionmentioning
confidence: 99%